PsycEXTRA Dataset 2013
DOI: 10.1037/e627722013-426
|View full text |Cite
|
Sign up to set email alerts
|

Personality and emotion regulation strategies

Abstract: The emotions has many important functions in our life such as in relation of interpersonal communication, and health. In interpersonal communicative function aimed to signal to other information about internal state. Emotions manifests in specific cognitive, behavioural, and physiological reactions, thus closely related to health. There is wide variety of ways for individuals to regulate their emotion. In this regard, there are two kinds of emotion regulation strategy; first Antecedent-focused emotion regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
4
0
4
Order By: Relevance
“…This may be expected given that an individual with a high score in NS typically seeks out and enjoys new or novel experiences, ideas and innovative activities. Extraversion and Openness of the five factor model (McCrae & John, 1992) which share a similar conceptual basis with NS are known to be correlated with the use of adaptive emotion regulation strategies (Aluja & Blanch, 2011;Hassani et al, 2008;Kokkonen & Pulkkinen, 2001;Purnamaningsih, 2017;Sadr, 2016;Sohn & Yoo, 2011). However, one of the four sub-dimensions of the NS temperament is impulsivity and impulsivity is typically not associated with adaptive emotion regulation (Schreiber, Grant, & Odlaug, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be expected given that an individual with a high score in NS typically seeks out and enjoys new or novel experiences, ideas and innovative activities. Extraversion and Openness of the five factor model (McCrae & John, 1992) which share a similar conceptual basis with NS are known to be correlated with the use of adaptive emotion regulation strategies (Aluja & Blanch, 2011;Hassani et al, 2008;Kokkonen & Pulkkinen, 2001;Purnamaningsih, 2017;Sadr, 2016;Sohn & Yoo, 2011). However, one of the four sub-dimensions of the NS temperament is impulsivity and impulsivity is typically not associated with adaptive emotion regulation (Schreiber, Grant, & Odlaug, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed of personality, for example, have reported that those high in Neuroticism tend to use maladaptive emotion regulation strategies, while individuals high in Extraversion and Openness use adaptive emotion regulation strategies (Hassani, Azadfallah, Tabatabaie, & Ashayeri, 2008;Kokkonen & Pulkkinen, 2001;Purnamaningsih, 2017;Sadr, 2016;Sohn & Yoo, 2011). However, personality also consists of psychosocial characteristics within an individual that determine behavioral, emotional and cognitive responses to internal and environmental stimuli that extend beyond temperament or stable automatic emotional responses (Cloninger, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Bu bulgu önceki çalışmalar ile de uyumludur (Balzarotti vd., 2010;Cabello vd., 2013;Gresham & Gullone, 2012;Haga vd. 2009;Liu vd., 2017;Páez, Mendiburo Seguel & Martínez-Sánchez, 2013;Purnamaningsih, 2017;Sadr, 2016;Shi vd., 2018;Vater & Schröder-Abé, 2015). Bastırma alt ölçeği ile kişilik özelliklerini ölçen diğer dört alt ölçekten herhangi biri arasında anlamlı ilişki tespit edilmemiştir.…”
Section: öLçüt Bağıntı Geçerliğine ġLiģkin Bulguların Tartıģılması Depresyon Ve Kiģilik öZellikleri Ile Duygu Düzenleme Arasındaki ġLiģkiunclassified
“…Wagstaff and Hanton (2013: 477) defined emotion regulation as being 'capable of keeping emotions under sufficient control to allow for interpersonal relatedness and sociability, prosocial initiatives when appropriate, sympathy toward others, personal assertiveness when needed, and/or other indices of successful functioning'. Some of the literature in emotion regulation seek effective emotion management strategies (Thiel et al, 2013;Akçay and Çoruk, 2012) suggested approaches to effective emotion regulation; Lively and Weed (2014) explained sociological insights into what is emotion management; Wagstaff et al (2013) aimed to improve the practice of individuals by providing an intervention to develop emotional abilities and strategies; Purnamaningsih (2017) and Turliuc and Bujor (2013) examined determinants and consequences of emotional management and Berking et al (2010) focused on the possibility of emotion management as a skill which can be enhanced by training. Improving emotion management ability is important because otherwise emotion dysregulation will lead to hopelessness, dissatisfaction, hypertension, coronary heart disease; even accelerate cancer progression and failure correspondingly (Gross, 1989;Pennebaker, 1990;Walumbwa et al, 2010;Vatan et al, 2014).…”
Section: Emotion Regulationmentioning
confidence: 99%